Macrophage extracellular traps require peptidylarginine deiminase 2 and 4 and are a source of citrullinated antigens bound by rheumatoid arthritis autoantibodies - Bashar, S. Janna; Holmes, Caitlyn L.; Shelef, Miriam A. (Frontiers in Immunology, 2024)
Introduction Anti-citrullinated protein antibodies (ACPAs) are a hallmark of rheumatoid arthritis, but the sources of citrullinated antigens as well as which peptidylarginine deiminases (PADs) are required for their production remain incompletely defined. Here, we investigated if macrophage extracellular traps (METs) could be a source of citrullinated proteins bound by APCAs, and if their formation requires PAD2 or PAD4. Methods Thioglycolate-induced peritoneal macrophages from wild-type, PAD2-/-, and PAD4-/- mice or human peripheral blood-derived M1 macrophages were activated with a variety of stimulants, then fixed and stained with DAPI and either anti-citrullinated histone H4 (citH4) antibody or sera from ACPA+ or ACPA- rheumatoid arthritis subjects. METs were visualized by immunofluorescence, confirmed to be extracellular using DNase, and quantified. Results We found that ionomycin and monosodium urate crystals reliably induced murine citH4+ METs, which were reduced in the absence of PAD2 and lost in the absence of PAD4. Also, IgG from ACPA+, but not ACPA-, rheumatoid arthritis sera bound to murine METs, and in the absence of PAD2 or PAD4, ACPA-bound METs were lost. Finally, ionomycin induced human METs that are citH4+ and ACPA-bound. Discussion Thus, METs may contribute to the pool of citrullinated antigens bound by ACPAs in a PAD2- and PAD4-dependent manner, providing new insights into the targets of immune tolerance loss in rheumatoid arthritis.